Perpendicularly stacked array of PTFE nanofibers as a reinforcement for highly durable composite membrane in proton exchange membrane fuel cells. (October 2022) - Hwang, Chang-Kyu; Lee, Kyung Ah; Lee, Jiyoung; Kim, Youngoh; Ahn, Hyunchul; Hwang, Wontae; Ju, Byeong-Kwon; Kim, Jin Young; Yeo, Sang Young; Choi, Joonmyung; Sung, Yung-Eun; Kim, Il-Doo; et al.
Abstract: The configuration of reinforced composite membrane (RCM), composed of porous polytetrafluoroethylene (PTFE) as a mechanical reinforcement and perfluorosulfonic acid (PFSA) as a proton conductive polymer, has gained a large interest due to its promisingly high performance for polymer electrolyte membrane (PEM) fuel cells. However, the inaccessible polymeric nanocomposites in preparing RCMs are still faced with critical challenges associated with immiscible interactions between hydrophilic sulfonate groups in PFSA and the hydrophobic nanoporous PTFE matrix. Herein, we report a well-refined and facile fabrication strategy for producing a cross-aligned PTFE (CA-PTFE) framework. The electric-field guided electrospinning enables the creation of unique micron-scale, grid-type PTFE matrix, which is synthesized by annealing of electrospun conjugated polymers, resulting in the removal of carrier polymer and the formation of continuous fibrious structure via fusion of PTFE particles. The CA-PTFE RCM embodying uniformly impregnated PFSA in a grid-type PTFE matrix, facilitates hydration of the membranes, with minimal swelling and efficient diffusion of protons through concentrated sulfonate groups. The CA-PTFE RCM adopted cell showed outstanding fuel cell currents during both low and high humidity operation, with a current density of 1.38 A cm −2 at 0.6 V and maximum power density of 0.85 W cm −2 under RH 100% condition. Furthermore, the CA-PTFE RCM was able to achieve a long-lasting single-cell operation with a significantly low hydrogen crossover (less than 5 mA cm −2 at 0.4 V) even after 21, 000 wet/dry cycles, which surpasses the standard of membrane durability for transportation application. The rational design of fibrous PTFE reinforcements opens up new engineering opportunities for the future development of high-stability PEM fuel cells. Graphical Abstract: ga1 Highlights: Cross-aligned PTFE (CA-PTFE) framework is synthesized via electric-field guided electrospinning and subsequent calcination. As a reinforcement, micron-scale patterned CA-PTFE framework is beneficial for the PFSA impregnation and the proton conduction. CA-PTFE reinforced composite membrane shows the outstanding current density and exceptional durability in PEM fuel cells.